The alleged transmission of Greek thinking concepts into Arabic grammar: is it still relevant? - Yaacob, Solehah@Nik Najah Fadilah (2011)
WHY I CHOSE THIS TOPIC TO BE DISCUSSED IN THIS CONFERENCE? BECAUSE BEFORE 20TH CENTURY THE WEST and ORIENTALIST BELIEVED ON THE INFLUENCE OF GREEK ON ARABIC GRAMMAR. BECAUSE BEFORE 20TH CENTURY THE WEST and ORIENTALIST BELIEVED ON THE INFLUENCE OF GREEK ON ARABIC GRAMMAR. HOWEVER IN THE MID OF 20TH CENTURY WHEN THE RENAISSANCE OF LANGUAGE DEVELOPMENT INTRODUCED BY NOAM CHOMSKY , THE CLAIM OR THE ALLEGED TRANSMISSION FROM GREEK INTO ARABIC GRAMMAR UNACTIVE.The paper consists of three sub topics, they are:1)The first encounter with Ancient Greek Thinking 2)The formal development of Greek Grammar The opponents of a Greek influence on Arabic Grammar OUR DISCUSSION WILL CONCENTRATE ON PART 3 WHICH IS The opponents of a Greek influence on Arabic Grammar